Host Suitability of House Fly, Musca domestica (Diptera: Muscidae), Pupae Killed by High or Low Temperature Treatment for a Parastoid, Spalangia endius (Hymenoptera: Pteromalidae) - Kohei Ogawa; Katsura Ito; Tatsuya Fukuda; Shin-ichi Tebayashi; Ryo Arakawa (The Scientific World Journal)
The objective of this study was to establish a high quality progeny production system for the house fly parasitoid, Spalangia endius (Hymenoptera: Pteromalidae), by stockpiling hosts. We performed two host killing methods before host storage: (i) heat-killed by 30 min exposure to 50°C or (ii) freeze-killed by 10 min exposure to −80°C. The average number of parasitoids that emerged from nonstored house fly pupae after heat- or freeze-killing was not significantly different from live pupae. When house fly pupae stored at −20°C after heat-killing were supplied to S. endius, progeny production was significantly less than live pupae. Moreover, productivity became very low when house fly pupae refrigerated at 3°C after heat- or freeze-killing were supplied to S. endius. On the other hand, when house fly pupae stored at −80°C for 1 year after heat-killing were supplied to S. endius, the average number of parasitoids that emerged was not significantly different from live pupae. The average number of parasitoids that emerged from freeze-killed hosts kept for more than 8 weeks at −80°C was significantly fewer than live pupae. Thus, this study clarified that a higher-quality host can be maintained not only by simply storing at –80°C but also by adding heat treatment before storage.